Benjamin Rubinstein on X (X (formerly Twitter), 2023)
That document calls for the creation of a “New Middle East” by, among other things, “weakening, containing, and even rolling back Syria” and “removing Saddam Hussein from power in Iraq — an important Israeli strategic objective in its own right.” As is known now, both of those…
Keywords: 911